Bioactive food as dietary interventions for arthritis and related inflammatory diseases - Watson, Ronald R. (Ronald Ross); Preedy, Victor R. (Bioactive foods in chronic disease states., 2013)
While diet has long been recognized as having potential to alleviate symptoms of inflammatory diseases including arthritis, lupus and fibromyalgia, research indicates that specific foods offer particular benefits in preventing or mitigating specific symptoms. Bioactive Food as Dietary Interventions for Arthritis and Inflammatory Diseases is the only available resource focused on exploring the latest advances in bioactive food research written for the scientist or professional audience. The only single-volume resource for scientists and professionals seeking information on how bioactive foods may assist in the treatment of inflammatory diseaseIncludes coverage of probiotics, prebiotics, and polyphenols. Convenient, efficient and effective source that allows reader to identify potential uses of compounds - or indicate those compounds whose use may in fact be of little or no health benefit. Documents foods that can affect inflammatory disease and ways the associated information could be used to understand other diseases, which share common etiological pathways.